What Can Requirements Engineering Do for Emerging System of Systems? Case of Smart Local Energy - Chitchyan, Ruzanna (IEEE/ACM International Conference on Software Engineering: Software Engineering in Society (Online), 2024)
As software solutions permeate the whole spectrum of human activities, many software systems previously developed to address specific issues suddenly find themselves becoming parts of interlinked and inter-dependent complex systems. This paper discusses a case study of such emergent convergence of software-rich socio-technical systems into an interconnected and integrated energy system-of-systems and outlines some areas where the Requirements Engineering discipline can help guide such a transition.Lay AbstractSoftware is becoming integrated in all areas of human activities (e.g., bus timetabling and home heating). Solutions that support such distinct activities are now becoming interlinked into complex systems which impact each other (e.g., both electric bus charging and home heating solutions need to balance with electricity grid). This paper discusses a case study of such emerging interdependence for energy systems and outlines where the Requirements Engineering discipline can facilitate better integration.CCS CONCEPTS*Software and its engineering → Design patterns; Ultra-large-scale systems;*Human-centered computing → Empirical studies in collaborative and social computing;*Applied computing → Cross-organizational business processes.